Vitamin B12 in Dermatology: A Review (International Journal of Food and Nutritional Sciences, 2022)
The water-soluble vitamin B12, often known as cobalamin, is crucial for the haematological and neurological systems and has a complicated connection with the skin. Dermatological symptoms caused by altered cobalamin levels may point to a vitamin shortage or excess. Cobalamin's biology and metabolism are intricate, and disorders may be linked to changes in this metabolic pathway. The most frequent cutaneous signs of cobalamin insufficiency are hyperpigmentation, followed by changes to the hair, nails, and mouth, including glossitis. In addition, an excess or shortage of cobalamin has been linked to a number of dermatological disorders, such as vitiligo, aphthous stomatitis, atopic dermatitis, and acne. Acne, rosacea, allergic reactions at the injection site, and anaphylaxis are some of the cutaneous side effects of cobalamin therapy. Patients with cobalt sensitivity have been known to experience cutaneous symptoms after taking cobalamin replacement therapy because cobalt is a component of cobalamin.